MIGRATION AS A REPRESENTATION OF SELF-TRANSFORMATION (SEMIOTIC READING OF IMAM SYAFI'I'S POEM ENTITLED "MIGRATION") - Ahmad Rais TM; Randy Randy (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Poetry is an expressive medium imbued with profound symbols and meanings, particularly within the classical Islamic literary tradition. One popular poem attributed to Imam Syafi'i raises the theme of wandering, explicitly encouraging one to leave one's hometown in search of knowledge, experience, and character development. This article aims to examine the poem through a semiotic approach to uncover the symbolic representation of wandering as a process of self-transformation. The research method used is a qualitative-descriptive approach with Roland Barthes's semiotic analysis at the levels of denotation, connotation, and myth, complemented by Michael Riffaterre's approach through the mechanisms of displacing, distorting, and creating of meaning. The analysis shows that symbols such as flowing water, a lion leaving its den, an arrow, and the sun represent the values of dynamism, courage, potential, and change. Wandering in this context is not merely a change of place, but an existential journey toward intellectual and spiritual maturity. These symbols also reflect the principles of Islamic education that emphasize the importance of the mobility of knowledge and manners. These findings indicate that Imam Syafi'i's poetry has philosophical depth and an indirect expression structure that is relevant in shaping the character of lifelong learners.